terraqueous: An Epistle for Harriet Ann Jacobs - Lanier, Michelle (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
Harriet Ann Jacobs, born enslaved in North Carolina, was more than a fugitive freedom seeker. She was also known, loved, and held by Black South ecosystems of witness. Michelle Lanier archivally and ecologically roots the epistolary poem, ‘terraqueous,’ in an effort to shrink the distance between the commemorative echoes of Jacobs’s story and the soils and waters that held her first breaths and acts of resistance.